Old Polish food and cuisine as elements of poetic imagery in Wespazjan Kochowski’s “Ogród Panieński” - Pikul, Aleksandra (Melusine. Old Literature and Culture, 2025)
In the Baroque era, the old Polish cuisine was characterized by various cooking methods and a fondness for unconventional flavour combinations. Her character was close to the literature of that period, which aimed to surprise the audience. This paper aims to identify thematic groups related to culinary metaphors and discuss examples of its use in Wespazjan Kochowski’s “Ogród Panieński” (“Garden of the Blessed Virgin Mary”). The highlighted groups include: food, culinary space, taste, and the titles associated with the role of the Mother-Nourisher. An important aspect in this context will also be identifying the spiritual messages concerning the Mother of God for the faithful of the Catholic Church. An analysis of this work will primarily allow us to observe how the poet combines Baroque aesthetics with Mariological themes.